Keeping up with the new normal: Analyzing the impact of remote work with the moderating role of demographics on work-life balance and job performance of employees From Red Lion Summit Life Insurance Agency - Arellano, Jasper Kim N. (Animo Repository, 2022)
How people live and work has changed significantly as a result of the COVID-19 disaster. Many employees and businesses were compelled to switch to remote work for the first time as a result of the epidemic, without any prior planning. Due to restrictions that made it difficult for them to operate, businesses in the Philippines were forced to temporarily close. This paper aims to determine the impact of remote working on an employees' work-life balance and job performance. With the aim of identifying the relationships and effects between work-life balance and job performance of employees' efforts measured collectively and individually through google form questionnaires distributed to 124 employees of Red Lion Summit Life Insurance Agency, an insurance company, this multivariate study introduces a conceptual model. Additionally, it is suggested in this article that the elements of remote working's internal and external features are linked to employees' work-life balance and job performance, which is influenced by their demographics.